2013
DOI: 10.1158/0008-5472.can-13-0578
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 Proteins Modulate the ETS Transcription Factor ETV1 in Prostate Cancer

Abstract: Overexpression of the ETS-related transcription factor ETV1 can initiate neoplastic transformation of the prostate. ETV1 activity is highly regulated by phosphorylation, but the underlying mechanisms are unknown. Here we report that all 14-3-3 proteins, with the exception of the tumor suppressor 14-3-3σ, can bind to ETV1 in a condition manner dictated by its prominent phosphorylation site S216. All non-σ 14-3-3 proteins synergized with ETV1 to activate transcription of its target genes MMP-1 and MMP-7, which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…YWHAE is among the 14-3-3 proteins that regulate the ETV1 transcription factor in PCa [26]. TRFC was shown originally to be significantly induced in DU145 cells [27], CORO1C/coronin was found to be induced in androgen-insensitive PCa [28] and S100A16 appears to be upregulated only in metastatic tumor cells [29].…”
Section: Resultsmentioning
confidence: 99%
“…YWHAE is among the 14-3-3 proteins that regulate the ETV1 transcription factor in PCa [26]. TRFC was shown originally to be significantly induced in DU145 cells [27], CORO1C/coronin was found to be induced in androgen-insensitive PCa [28] and S100A16 appears to be upregulated only in metastatic tumor cells [29].…”
Section: Resultsmentioning
confidence: 99%
“…We found that 3 isoforms are bound strongly: 14-3-3, which is consistent with our previous studies (23), plus 14-3-3ε and 14-3-3. These isoforms all have important roles to play in diverse aspects of cellular homeostasis (27)(28)(29), and it is now imperative to ascertain how E6 interaction with these isoforms affects E6 activity and 14-3-3 functions. These findings have also facilitated a series of studies to assess the ability of the other high-risk HPV E6 oncoproteins to interact with 14-3-3 in a phosphorylation-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we recently showed that this phosphorylated E6 could instead interact with 14-3-3 (23), a phospho-serine/threonine binding protein (26). There are seven different isoforms of 14-3-3, which play diverse roles in the regulation of cellular homeostasis, many of these functions being relevant for cancer development (27)(28)(29). This suggests that the E6 PBM is actually bifunctional, mediating interaction with either PDZ domain-containing substrates or 14-3-3 family members, depending upon the E6 phosphorylation status.…”
mentioning
confidence: 99%
“…Numerous erythroblastosis virus E26 transformation-specific (ETS) transcription factors contribute to the development of cancers (Oh, 2013; Reddy, 1991; Shin, 2013). ETV1, ETV2, ETV3, ETV4, Fli-1, and ERG are examples of these factors (Fang, 2014; Rao, 1987; Reddy, 1989; Spans, 2013).…”
Section: Introductionmentioning
confidence: 99%